Promotion and Development of Vocational Personnel Education in Tourism and Service Sectors of Thai-Cambodian Border Area Ubon-Ratchathanai and Sisaket Provinces - Kobjaiklang, Chulaporn; Methawudthisakun, Thidsanu; Sadompruk , Apimuk; Thaijongrak, Natthaporn (Journal of Modern Learning Development, 2020)
The objective of this article to study to finding guidelines for promote knowledge and skills of vocational personnel in cooperation with Thai-Cambodian agencies and (2) to guidelines for a sustainable cooperation model for tourism development in the Thai-Cambodian border areas Ubon Ratchathani and Sisaket Provinces. This study used qualitative research comprising of in-depth interview and focus group discussion were undertaken with key informants with are the relevant vocational personnel education, and use the information from the interviews was then analyzed by content analysis.The research findings showed that: 1.Finding guideline to promote knowledge and skills of vocational personnel in cooperation with Thai-Cambodian agencies in Ubon Ratchathani and Sisaket Provinces. Such as, the institutes has encouraged the students to learn and practice foreign language skills. The part as for the teachers were found that encouraged to learn foreign languages and study new knowledge, as well as encouraging teachers to train to increase teaching skills. Professional skills in order to increase teaching expertise in the professional field. The part as for the executives of Vocational Institutes were found that cooperation in network development between vocational institutes and outside agencies in order to participate in the development of teaching and learning curriculum, internships and student development by promoting other professional skills to teachers and students. 2.The guidelines for a sustainable cooperation model for tourism development in the Thai-Cambodian border areas Ubon Ratchathani and Sisaket Provinces such as, the forms of cooperation that occur within vocational institutions to create the way for sustainable development together must occur in all sectors. Other agencies related to education and tourism within the province and then extended to other neighboring provinces to be forms of cooperation with the Cambodian side, that at the local level there should be a continuous relationship between leaders in border areas both sides